2019
DOI: 10.1016/j.idcr.2019.e00548
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli endocarditis of a native mitral valve

Abstract: Escherichia coli ( E.coli ) is a rare cause of endocarditis, although is a common causative agent of bacteremia. An 89-year-old woman presented with recurrent episodes of fever and persistent E. coli bacteremia with 3-month duration, despite antimicrobial therapy. At first, a urinary tract infection was diagnosed and later a mycotic aneurysm of the abdominal aorta was found and required an endovascular repair. The persistence of fever and the evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Additionally, it has been shown that some co-morbidities, such as diabetes, malignancy, excessive alcohol consumption, hemodialysis could predispose to E. coli infective endocarditis [ 1 ]. Several studies have reported, that among the four heart valves, the native mitral valve seems to be the most frequently affected endocarditis caused by E. coli [ 1 , 4 10 ].. Here, we report a rare case of E. coli O2:K7:H6, B2, ST141 associated with urinary tract infection (UTI) and endocarditis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, it has been shown that some co-morbidities, such as diabetes, malignancy, excessive alcohol consumption, hemodialysis could predispose to E. coli infective endocarditis [ 1 ]. Several studies have reported, that among the four heart valves, the native mitral valve seems to be the most frequently affected endocarditis caused by E. coli [ 1 , 4 10 ].. Here, we report a rare case of E. coli O2:K7:H6, B2, ST141 associated with urinary tract infection (UTI) and endocarditis.…”
Section: Discussionmentioning
confidence: 87%
“…Adhesins can play a key role in pathogenic process. As suggested by Nogueira et al some of these factors could enable E. coli to adhere to cardiac valves [ 4 ]. The present isolate was positive for at least two adhesins, P fimbriae ( papA _F12 and papC ) and S fimbrial/F1C fimbriae ( focC, focI, sfaD, sfaE and sfaS ) that are frequent in uropathogenic human isolates and extraintestinal avian pathogenic E. coli (APEC) isolates.…”
Section: Discussionmentioning
confidence: 99%